Bioprocessing Butanol into More Valuable Butyl Butyrate - Xin, Fengxue; Zhang, Wenming; Jiang, Min (Trends in biotechnology (Regular ed.), 2019)
The toxicity of butanol to microbial cells makes it difficult to scale-up the acetone–butanol–ethanol (ABE) fermentation process. Bioconversion of butanol into more valuable and nontoxic short-chain esters, such as butyl butyrate which is widely used in the food, beverage, and biofuel sectors, offers a promising alternative.